Evidence of multiband superconductivity in the β-phase Mo1−xRex alloys. (7th January 2015) - Sundar, Shyam; Sharath Chandra, L S; Chattopadhyay, M K; Roy, S B
Abstract: We present a detailed study of the superconducting properties in the β -phase Mo1− x Re x ( x  = 0.25 and 0.4) solid solution alloys pursued through magnetization and heat capacity measurements. The temperature dependence of the upper critical field H C 2 ( T ) in these binary alloys shows a deviation from the prediction of the Werthamer–Helfand–Hohenberg (WHH) theory. The temperature dependence of superfluid density estimated from the variation of lower critical field H C 1 with temperature, cannot be explained within the framework of a single superconducting energy gap. The heat capacity also shows an anomalous feature in its temperature dependence. All these results can be reasonably explained by considering the existence of two superconducting energy gaps in these Mo1− x Re x alloys. Initial results of electronic structure calculations and resonant photoelectron spectroscopy measurements support this possibility and suggest that the Re-5d like states at the Fermi level may not intermix with the Mo-5p and 5s like states in the β -phase Mo1− x Re x alloys and contribute quite distinctly to the superconductivity of these alloys.